Impact of offline experiences on consumer decisions: Balanced vs. unbalanced social exchange in switching to online health services - Teng Wang; Yongqiang Sun (Digital Health)
Objective The diffusion of online health consultations (OHCs) depends on consumers switching from offline to online channels; consumers’ offline experience on health servicer determines their decisions. Our research aims to address this gap in the literature by examining how offline experiences of doctor–patient interactions influence online switching intentions. Methods We conducted online surveys, and 662 samples were collected and analysed the data using structural equation model via SmartPLS. Drawing on social exchange theory, we divided offline experience into balanced (discrete and relational social exchange) and unbalanced social exchange (doctor power and patient compliance). In accordance with the dedication-constraint model, perceived value and offline habit were defined as dedication and constraint factors, respectively; the influence of offline experience on both dedication and constraint factors was revealed. Moreover, we introduced the moderation effect to reveal the boundary of the effect of offline experience. Results Our findings showed that balanced social exchange increases consumers’ perceived value towards OHC, whereas unbalanced social exchange increases offline habit. Additionally, we observed a positive association between perceived value and the intention to switch, whereas offline habits had a negative impact. Online trust, as a moderator, strengthens the relationship between balanced exchange and perceived value and weakens the relationship between unbalanced exchange and offline habits. These results establish a theoretical framework for comprehending cross-channel switching in online health service marketing. Conclusions Since offline experience of doctor–patient interactions influences consumers’ decisions, it is critical for online health service platforms to apply cross-channel integration strategy rather than depend on online channels alone.